Pharmacological modulation of apoptosis and autophagy in pancreatic cancer treatment - Stanslas, Johnson; Islam, Mohammad Kaisarul; Selvarajoo, Nityaa; Sagineedu, Sreenivasa Rao; Lian, Ho Kok; Lim, Jonathan Chee Woei (Bentham Science Publishers, 2022)
Pancreatic cancer is a fatal malignant neoplasm with infrequent signs and symptoms until a progressive stage. In 2020, GLOBOCAN reported that pancreatic cancer accounts for 4.7% of all cancer deaths. Despite the availability of standard chemotherapy regimens for treatment, the survival benefits are not guaranteed because tumor cells become chemoresistant even due to the development of chemoresistance in tumor cells even with a short treatment course, where apoptosis and autophagy play critical roles. This review compiled essential information on the regulatory mechanisms and roles of apoptosis and autophagy in pancreatic cancer, as well as drug-like molecules that target different pathways in pancreatic cancer eradication, with an aim to provide ideas to the scientific communities in discovering novel and specific drugs to treat pancreatic cancer, specifically PDAC. Electronic databases that were searched for research articles for this review were Scopus, Science Direct, PubMed, Springer Link, and Google Scholar. The published studies were identified and retrieved using selected keywords. Many small-molecule anticancer agents have been developed to regulate autophagy and apoptosis associated with pancreatic cancer treatment, where most of them target apoptosis directly through EGFR/Ras/Raf/MAPK and PI3K/Akt/mTOR pathways. The cancer drugs that regulate autophagy in treating cancer can be categorized into three groups: i) direct autophagy inducers (e.g., rapamycin), ii) indirect autophagy inducers (e.g., resveratrol), and iii) autophagy inhibitors. Resveratrol persuades both apoptosis and autophagy with a cytoprotective effect, while autophagy inhibitors (e.g., 3-methyladenine, chloroquine) can turn off the protective autophagic effect for therapeutic benefits. Several studies showed that autophagy inhibition resulted in a synergistic effect with chemotherapy (e.g., a combination of metformin with gemcitabine/ 5FU). Such drugs possess a unique clinical value in treating pancreatic cancer as well as other autophagy-dependent carcinomas.